(untitled) (Zaporizhzhia Historical Review, 2021)
The purpose of article is the analysis of the publications (1895-1914) of the leaders and activists of Ukrainian Democratic-Radical Party, which concerned questions of a nation, national consciousness, Ukrainian national idea, periods and essence of process of national revival, roles of intelligentsia and its mutual relation with the people. The analysis will be carried out in a context of the modern concepts of formation of nations.